Numerical analysis of transport properties of ZnO based Schottky diode. (13th April 2021) - Ahmed, Nosheen; Khan, Azam; Hussain, Mushtaque
Abstract: Since numerical methods allow us to generate data faster than experimental methods in less time and with less effort, therefore in the presented work two well-known numerical methods known as Newton-Raphson and Gauss-Seidel were employed to compute electrical parameters of electronic devices at highly sensitive temperature from 300 K to 1000 K to discuss the significance of these parameters on the competency of devices. ZnO based Schottky diode has been considered due to the substantial properties of ZnO which are very crucial in the invention of high-quality devices. The investigations were focused on exploring the consequences of highly sensitive temperature on electrical parameters like ideality factor, saturated current, donor concentration, built in potential and height of barrier of Schottky diode. All parameters were computed by applying Newton-Raphson and Gauss-Seidel method on well-known thermionic emission model and capacitance-voltage equations.